The Role of the Family Environment as an Effort to Provide Learning Motivation in Improving Student Learning Outcomes - Iswan; Aurelly, Elsa (Advances in Social Sciences Research Journal, 2023)
With the title: The Role of The Family Environment as an Effort to Provide Learning Motivation in Improving Student Learning Outcomes, this research was conducted at SDN 04 Ciputat, South Tangerang. Indonesian. This research Method is with a quantifiable quantifiable approach. The results of this study show that based on the results of the analysis and results statistical tests that variable (X) the role of the family environment has asignificant correlation to the variable (Y) Improving Student Learning Outcomes. Based on the results of the Wilcoxon test, it showed a value of 0.000<0.05 and a correlation value/relationship R of 0.518. The results obtained a coefficient of determination Rsquare of 0.268, very meaningful that the family environment independent variable of the family environment towards motivating children was 27,0%. Meanwhile, the results of the validity test of variable X (The Role of the Family Environment), and variable Y (Improving Student Learning Outcomes), at SDN 04 Ciputat, South Tangerang. Indonesia, determined Rtable by 0.299, with the leadgan Df=N-2, df=88-2=86, Rtable from 86 thereis 0.299. Then it can be concluded that as many as 4 items out of the 24 items the role the family environment variable (X) are said to be invalid because Rcount<Rtable no item (1,5,17,21), and 20 items are said to be valid Rcount>Rtable, and for child motivation variables (Y) have the value of 3 invalid items no item (5,17,20) and 23 items are declared valid because rcount>rtable. The results of the hypothesis test, the family environment is very correlated to increase learning motivation because the motivation needed by children in learning does not only come from within the child/intrinsic but also comes from the child’s external motivation/ectrinsic, one that canadd extrinsic motivation ason is the encouragement given by the family can equip children so that they have high learning motivation, besides that harmony in the family creating a comfortable environment will affect the success of students in learning.